The Impact of Mobile Seamless Learning Strategies and Digital Literacy on Students' Concept Mastery in Islamic Education Courses - Zikri, Ihsan (AFKARINA: Jurnal Pendidikan Agama Islam, 2023)
This study aims to investigate the impact of the Mobile Seamless Learning Strategy and digital literacy on students' concept mastery in Islamic Education. The growing development of science, along with social, cultural, and economic growth, demonstrates the positive direction of technology and information development in Indonesia. However, the disconnection between formal and non-formal education has created a lack of coherence among educators, making it difficult for students to master learning concepts. Limited classroom hours necessitate alternative solutions, such as the Mobile Seamless Learning Strategy, which bridges in-school and out-of-school education through digital media. Digital literacy is also considered a critical factor in this process. The research method employed is a literature study, gathering relevant data from books, journals, dictionaries, magazines, and other sources without the need for field research. The findings suggest that this approach can significantly enhance students' understanding of learning material, contributing to the achievement of educational goals.